2006
DOI: 10.1007/s00122-006-0370-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genetic loci associated with ear-emergence in bread wheat

Abstract: A doubled haploid population constructed from a cross between the South Australian wheat cultivars 'Trident' and 'Molineux' was grown under winter field conditions, under field conditions over summer and under artificial light both with and without vernalisation. The duration from planting to ear-emergence was recorded and QTL associated with heading date were detected using a previously constructed genetic linkage map. Associations were shown with chromosomal regions syntenous to previously identified photope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
44
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 25 publications
9
44
1
Order By: Relevance
“…The 2BS region was associated with positive and negative effects on ANT, GW and GY in the present study; comparative mapping suggests that it is the same region as identified in several published studies, which contains QTLs for anthesis, height, grain weight and grain yield (Verma et al 2004;Quarrie et al 2005;Kuchel et al 2006;Rebetzke et al 2008;McIntyre et al 2010), and Ppd-B1 (Mohler et al 2004). Similarly, the 7BL region was associated with all four traits in this study.…”
Section: Comparative Analyses Confirm Preferential Retention Of Chromsupporting
confidence: 80%
See 3 more Smart Citations
“…The 2BS region was associated with positive and negative effects on ANT, GW and GY in the present study; comparative mapping suggests that it is the same region as identified in several published studies, which contains QTLs for anthesis, height, grain weight and grain yield (Verma et al 2004;Quarrie et al 2005;Kuchel et al 2006;Rebetzke et al 2008;McIntyre et al 2010), and Ppd-B1 (Mohler et al 2004). Similarly, the 7BL region was associated with all four traits in this study.…”
Section: Comparative Analyses Confirm Preferential Retention Of Chromsupporting
confidence: 80%
“…Similarly, the 7BL region was associated with all four traits in this study. This also appears to be the same as the region identified as containing QTLs for anthesis and grain yield, by Kuchel et al (2006) and Quarrie et al (2005), respectively. In this study, a region on 1AL was associated with earlier flowering and reduced height; it appears to be the same as the anthesis QTL region identified by Kuchel et al (2006).…”
Section: Comparative Analyses Confirm Preferential Retention Of Chromsupporting
confidence: 75%
See 2 more Smart Citations
“…QTL were considered common to different environments when the corresponding chromosome peak positions were located within 20 cM. QHd.idw-3B QPht.idw-3A Kuchel et al 2006). It is worth noting that one of the major QTL detected in our study on chr.…”
Section: Discussionmentioning
confidence: 99%